Comparing a new visuospatial intervention administered 3 days after a trauma film to reduce the occurrence of intrusive visual memories: a single-center randomized, controlled trial in healthy participants - Matura, Jan-Martin; Kessler, Henrik; Holmes, Emily A.; Timmesfeld, Nina; Tokic, Marianne C.; Axmacher, Nikolai; Blackwell, Simon E.; Schmidt, Anna-Christine; Schweer, Johanna M.; Hippert, Charlotte; Apel, Lukas; Dieris-Hirche, Jan; et al. (Frontiers in Psychology, 2025)
IntroductionIntrusive memories occur frequently after potentially traumatic events and form a core symptom of posttraumatic stress disorder (PTSD) if they persist. The translational approach of visuospatial interventions tries to target those intrusive memories in order to reduce their frequency predominantly using an intervention including as one component the computer game Tetris. Despite promising results, the application of Tetris has critical drawbacks, e.g., potential commercial or copyright issues. Furthermore, it remains unclear whether it is this specific game or, as predicted by theory, a visuospatial task per se that leads to the effect. This study hence aims to compare the effect of Tetris with an alternative, bespoke visuospatial task: Mobilum developed for the current purpose.MethodsN = 120 healthy participants watched a trauma film and recorded their intrusive memories in a diary for 6 days. Three days after watching the film, they were randomized to 3 groups and after memory reactivation cue received either Tetris or Mobilum or Control (no task). Prior to intervention 8 participants reported zero intrusive memories to the film and were excluded from further analyses, therefore 112 participants were included in the analysis.ResultsA mixed Poisson regression model revealed that the Mobilum group had significantly less frequent intrusive memories after the intervention compared to the control condition (approximately 43%, p = 0.0013). There was no significant difference for the Tetris group compared to Control (17% less frequent, p = 0.3798).DiscussionOur results suggest that visuospatial tasks other than Tetris—in this case, Mobilum—can also lead to a reduction in intrusive memories when administered 3 days after a trauma film. This strengthens the assumption that it is not specifically the game Tetris, but rather the visuospatial nature of the task, that is responsible for the reduction. Aspects of further investigating the potential of Mobilum as well as clinical implications are discussed.